Protocol for a quasi experimental mixed method study on impact of intervention for improving Infant and Young Child Feeding (IYCF) practices in tribal block of Palghar District, Maharashtra, India through involvement of frontline workers - Suchitra Surve; Shraddha Kyatam; Shahina Begum; Bhavya M. K; Santosh Chaudhari; Sagar Patil; Shivshankar Timmanpyati; Purabi Mahajan; Ragini Kulkarni (PLoS ONE, 2026)
Introduction Infant and Young Child Feeding (IYCF) is crucial for child growth, especially in the first two years. Despite various government initiatives, nearly 35.5% of under-five children present with stunted growth in India as per NFHS-5 survey. Moreover, tribal areas like Palghar in India are most affected due to limited access to healthcare, poverty and knowledge gaps. While frontline workers such as Anganwadi Workers (AWWs) play a key role in IYCF promotion in community; gaps in their knowledge, counselling strategies and contextual barriers hamper the desired outcome. The study aims to assess the knowledge, attitude, and practices (KAP) of frontline workers and mothers on IYCF; and to develop and evaluate a context specific intervention package to improve IYCF practices for better health outcomes among young children. Methods A quasi-experimental mixed-methods study will be conducted over two years in three phases (baseline, intervention and post intervention) in the Ganjad PHC of Palghar District, Maharashtra. After qualitative assessment of frontline workers, a total of 460 mother-infant (6–12 months) dyads will be enrolled in baseline and post intervention through cluster sampling across 44 Anganwadi Centres. Baseline and endline IYCF practices will be collected using a structured questionnaire along with anthropometric assessment The intervention will include capacity building of frontline workers and mothers on IYCF Practices through Socio Behavioral Communication Change approach, preparation of pictorial booklets and charts, provision of hot cooked CF servings at Anganwadi Centers along with Iron, Calcium and Vitamin D supplementation. The quantitative data will be analyzed using descriptive and inferential statistics, and qualitative data thematically. Discussion This study proposes a community-based intervention to improve IYCF practices among tribal populations in Palghar District, Maharashtra. It integrates behaviour change communication with hot cooked meal provision at Anganwadi Centres through frontline workers. The approach emphasizes cultural relevance and sustainability, with potential to inform scalable strategies and policy within ICDS. Clinical trial registration CTRI/2024/06/068427 Registered on 06th June, 2024.